The roan antelope (Hippotragus equinus, Desmarest 1804), its ecology in the Waterberg Plateau Park - Erb, Karl Peter (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.